Study of Non-Notified Trade Agreements to the World Trade Organization: The Case of Asia and Pacific Region - Shintaro Hamanaka (Asian Development Bank (ADB), 2014)
"Cast light and evil will go away." This is the basic idea of the transparency exercise of regional trade agreements (RTAs) at the World Trade Organization (WTO). Information sharing on RTAs is critically important because monitoring is impossible without it. In order for us to see not only good but also evil RTAs, a light called "notification requirement" should reach them. In reality, however, it is too optimistic to assume that the light reaches all RTAs. There seem to be many ghosts living in the dark; no information on ghosts can be shared and none can confirm if they are really ghosts. This paper attempts to reveal those RTAs upon which the WTO fails to shed the light of the transparency exercise. While many studies have pointed out that there are many non-notified RTAs as a reservation in conducting analysis of RTAs, this is the first scholarly attempt to identify the comprehensive picture of non-notified RTAs, with an emphasis on the Asia and the Pacific. Because information on all RTAs notified to the WTO is included in the WTO RTA Database, gathering information on non-notified trade agreements is the key to understanding the universe of trade agreements.
hdl:11540/1292
Keywords: F15; F53; 330; non-notified RTAs; transparency; Committee on Regional Trade Agreements(CRTA); notification; World Trade Organization (WTO); systemic issues